Exploring fluorescent light energy as management option for canine superficial bacterial folliculitis - Marchegiani, Andrea; Spaterna, Andrea; Fruganti, Alessandro; Cerquetella, Matteo (Frontiers in Veterinary Science, 2023)
Superficial bacterial folliculitis (SBF) represents a common dermatological diagnosis in dogs that can be successfully managed with either topical and/or systemic treatments. In the present study we evaluated the efficacy of a fluorescent light energy (FLE) device as sole management for SBF. The same FLE device has been shown, as adjunct therapy to systemic antibiotic or alone, to effectively control clinical manifestation of interdigital furunculosis. Twenty dogs were randomized to receive FLE once (six dogs) or twice (six dogs) weekly in comparison with oral anti-biotic (eight dogs) until complete healing. FLE regimen was able to significantly reduce the time needed to clinical resolution for oral antibiotic, supporting owners’ compliance and welfare of dogs.